Kemampuan Rasio Keuangan dan Ukuran Perusahaan dalam Memprediksi Kinerja Keuangan - Tulasi, Daniel (Jurnal Widya Manajemen & Akuntansi, 2006)
The study investigates the power of financial ratios and firm's size in predicting financial performance of Textile and Apparel listed at Jakarta Stock Exchange. The data are analyze by using logic regression. The result indicates that current ratio, gross profit margin and firm's sizeb eiomi prediclorso f the firm's financial performance. The g Sodnesos ffit testu singH osmer and Lemeshowrc sr indicatei that nodel fiUed it 9t ,8% Ievelo f significance with NagdlkerkeR ' square is 60,8%o.T. he overall classification rate is 79,6%, it is greater than the naive classification rate of 50%.